Pendampingan LKS Tematik SD Khas Budaya Masyarakat Kota Wisata Batu Jawa Timur - Restian, Arina; Amelia, Delora Jantung; Saputra, Setiya Yunus (Khadimul Ummah, 2019)
Implementation, a community service program entitled "IbM Thematic Worksheets of Elementary Schools LKS Distinctive Culture of the City of Batu Tourism in East Java At SD Muhammadiyah 4 Batu City" this assistance began with a workshop on making thematic worksheets by highlighting the culture of Batu City. This program involves 4 lecturers as a service team and class I-VI teachers as participants of this activity. Prior to the implementation of the lecturers' activities, several coordinating meetings had been held to design community service and socialization activities to the school where the community service was held. This activity involves collaboration with partner schools / elementary schools. There is 1 school involved in this activity, namely SD Muhammadiyah 4 Batu, From the school the teacher appointed is grade I-VI. For the sake of the success of this partnership, teachers who will become training participants need to get strengthening of elementary thematic worksheets that are characterized by the culture of the people of Batu City, to preserve the local wisdom of Batu City. This LKS assistance is currently in the era of the industrial revolution 4.0, therefore we have strengthened the learning system in terms of local wisdom in the local area, Batu City, which is not only invited by students to abstract and imagine areas that have never been visited, the authors initiated to improve the city of stone as local wisdom and enter the material in the form of LKS. This worksheet consists of basic levels, low class to high class. The level of making these worksheets refers to the analysis of hots questions on the types of questions that we pack, so that the ability of students is fun to be able to live everyday, especially in stone city, as readers of our own products. This is related to the need for schools at the elementary school level.